A cross-cultural analysis of factors influencing choice in volunteering activities. Issue 1 (19th January 2015) - Offstein, Evan H.; Chory, Rebecca M.; Childers Jr, J. Stephen
Abstract : Purpose: – This study aims to offer insights into the contextual and situational variables that influence volunteering choices. Design/methodology/approach: – An analysis of European and US business students' volunteering experiences is performed. Cross-cultural and experiential outcomes are compared and contrasted at both the undergraduate and graduate levels. Findings: – A majority of volunteering decisions are made without thoughtful reflection, based on convenience in an effort to reduce personal hardship, and influenced heavily by institutional and organizational structures. Originality/value: – These results call into question the notion that volunteering-related choices are deeply personal, purposeful and/or reflective decisions. Moreover, the findings begin to explain why volunteerism continues to be dogged by labels such as "ineffective", "inefficient" or "lacking in value" when benchmarked against expectations.